2021
DOI: 10.3390/coatings11121466
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Physico-Chemical Properties of Antifungal Samarium Doped Hydroxyapatite Thin Films

Abstract: Samarium doped hydroxyapatite (Ca10−xSmx(PO4)6(OH)2, xSm = 0.5, 50SmHAp) is a very promising candidate to be used for different coatings in various dental and orthopedic implants. We report, for the first time, the obtaining of 50SmHAp thin films by a cost-effective method, namely spin coating. Thin films of 50SmHAp on silicon substrate have been analyzed by various techniques such as Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), atomic force microscopy (AFM), Metallograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…The antifungal assays also suggested that the 5EuHAp suspensions exhibited better antifungal activity compared to 5EuHAp coatings. These results are also in good agreement with previously reported studies regarding coatings that almost completely retain the antifungal effects of the suspensions used for their depositions [40,49]. The preliminary results obtained from the in vitro antifungal assays highlighted that both 5EuHAp suspensions and coatings present strong antifungal properties that are correlated with the incubation time.…”
Section: Resultssupporting
confidence: 91%
“…The antifungal assays also suggested that the 5EuHAp suspensions exhibited better antifungal activity compared to 5EuHAp coatings. These results are also in good agreement with previously reported studies regarding coatings that almost completely retain the antifungal effects of the suspensions used for their depositions [40,49]. The preliminary results obtained from the in vitro antifungal assays highlighted that both 5EuHAp suspensions and coatings present strong antifungal properties that are correlated with the incubation time.…”
Section: Resultssupporting
confidence: 91%
“…The antifungal activity was also obtained with the 0.05Sm-HAp NPs in suspension and not only with the coatings [ 112 ]. In fact, increasing the molar concentration of Sm up to 0.5 preserved antifungal activity against C. albicans when the coating was prepared and as a NPs suspension [ 113 ].…”
Section: Biological Role Of Hap and Its Substitution Ionsmentioning
confidence: 99%